The importance of social support in enhancing performance and well-being of Malaysia's Paralympic athletes - Azmi, K. N. E. M.; Khan, T. K. B. A. (Scientific Journal of Sport and Performance, 2025)
This study aims to study the experiences of elite wheelchair basketball players in Malaysia in regard to the social support that they have received and its effect on performance and well-being. The approach of use was qualitative, which adopted ethnographic methods, including observations and in-depth interviews with five elite athletes from a Paralympic Sports Excellence Centre located in Kg Pandan. The research revealed four primary types of social support obtained by athletes: These types of support vary along emotional, instrumental, informational, and appraisal dimensions. Additionally, this study pointed to teammates, coaches, family, and sports organizations and preceded the important role they play in protecting mental stability and athletic achievement; however, it highlighted problems such as the lack of continuity in the care after the post-program. Enhancing social support systems through comprehensive post-program activities and higher levels of logistical subsidies is needed to achieve the long-term development of Paralympic athletes, according to this study. Theory is enriched, policy is informed, and social awareness of the importance of social support within Paralympic sports is increased with these findings.